Use of dorsalis pedis artery flap in coverage of distal lower leg defects - Ghelani, Nilesh B.; Shah, Ankit; Patel, Dhruv V.; Tomar, Janvi; Rajgor, Darshil (International Journal of Research in Medical Sciences, 2023)
Soft tissue defect in the distal one third of leg have always posed a challenge for reconstructive surgeons. Such wounds are difficult to manage due the tenuous blood supply, limited subcutaneous cover over the tendons and bones. The aim of our study is to investigate the outcome of Dorsalis pedis artery flap for the coverage of such defects. In the present study, we share our clinical experience with the use of dorsalis pedis artery flap for the coverage of defect in the distal one third leg. This is a series of 4 cases where dorsalis pedis artery flap was used to cover lower one third defect. One case had focal squamous cell carcinoma due to long standing post burns contracture in distal one third of leg anteriorly. Other 3 cases had chronic non healing ulcer in the malleolar region. Patient outcome was assessed according to patients’ age distribution, duration of surgery, hospital stay, and post-operative complications. All 4 patients had excellent outcome with no major donor site complications, infection, and graft loss. Donor site was closed with split thickness skin graft. One patient developed a minor raw area over the dorsum of foot which healed secondarily. Although a potential risk in applying this flap is insufficient venous drainage, no problems with blood inflow or outflow were encountered in the present case series. The flaps survived, and the patient had good postoperative outcome. Hence dorsalis pedis flap can be used for the coverage of the distal foot as a good option.